Evaluating Planned Organizational Change: A Method for Assessing Alpha, Beta, and Gamma Change - Terborg, James R.; Howard, George S.; Maxwell, Scott E. (Academy of Management Review, 1980)
James R. Terborg, George S. Howard, Scott E. Maxwell, Evaluating Planned Organizational Change: A Method for Assessing Alpha, Beta, and Gamma Change, The Academy of Management Review, Vol. 5, No. 1 (Jan., 1980), pp. 109-121